(untitled) - Kolevzon, Alex (Philadelphia, 2002)
Comprehensive review of clinical psychiatry written from a student's perspective. Each topic is divided into three sections: 'The Basics,' 'Essential Features,' and 'Depth and Detail,' corresponding to a different point in the rotation. DNLM: Mental Disorders--Examination Questions.
Keywords: Psychiatry,Mental illness,Psychology, Pathological,Mental Disorders,Tâm thần học,Bệnh tâm thần,Tâm lý học, Bệnh lý,Rối loạn tâm thần